Secretome proteins as candidate biomarkers for aggressive thyroid carcinomas. Issue 5 (8th March 2013) - Chaker, Seham; Kashat, Lawrence; Voisin, Sebastien; Kaur, Jatinder; Kak, Ipshita; MacMillan, Christina; Ozcelik, Hilmi; Michael Siu, K. W.; Ralhan, Ranju; Walfish, Paul G.
<x xml:space="preserve">Abstract</x> Using proteomics in tandem with bioinformatics, the secretomes of nonaggressive and aggressive thyroid carcinoma (TC) cell lines were analyzed to detect potential biomarkers for tumor aggressiveness. A panel of nine proteins, activated leukocyte cell adhesion molecule (ALCAM/CD166), tyrosine‐protein kinase receptor (AXL), amyloid beta A4 protein, amyloid‐like protein 2, heterogeneous nuclear ribonucleoprotein K, phosphoglycerate kinase 1, pyruvate kinase isozyme M2, phosphatase 2A inhibitor (SET), and protein kinase C inhibitor protein 1 (14–3‐3 zeta) was chosen to confirm their expression in TC patients' sera and tissues. Increased presurgical circulating levels of ALCAM were associated with aggressive tumors (p = 0.04) and presence of lymph node metastasis (p = 0.018). Increased serum AXL levels were associated with extrathyroidal extension (p = 0.027). Furthermore, differential expression of amyloid beta A4 protein, AXL, heterogeneous nuclear ribonucleoprotein K, phosphoglycerate kinase 1, pyruvate kinase muscle isozyme M2, and SET was observed in TC tissues compared to benign nodules. Decreased nuclear expression of AXL can detect malignancy with 90% specificity and 100% sensitivity (AUC = 0.995, p < 0.001). In conclusion, some of these proteins show potential for future development as serum and/or tissue‐based biomarkers for TC and warrant further investigation in a large cohort of patients.